Duang: the semiotic interpretation and perception of the Bajau-Sama community in Sabah - Halina Sendera Mohd. Yakin,; Saidatul Nornis Hj. Mahali, (2008)
Sabah is not only famous for its beautiful and breathtaking fauna and flora, it is also known for its multiethnicity which has more than 40 different ethnic groups including the sub-ethnic groups. The second largest ethnic group in Sabah is the Bajau. This article will portray and explicate the non-verbal aspects of communication in the Bajau tradition, mainly on matters relating to the demise customs or the ngeduang ceremony. This study is conducted in Kota Belud where a sizeable Bajau community with their own culture and the size inhabited in that area. The demise customs or the death rituals are slightly similar to the demise customs of the Malay community. The content and presentation of duang has changed over time depending on the financial status, trend and life style of the people. The changes of the duang, either for the contents as well as the presentation have different covert meaning, depending on the wish of the duang owner and the interpretation and perceptian of duang recepient and guests.